Mitteilungen des Internationalen Bundes der Privatangestellten (IBP)
Continued by: Pressedienst. Internationaler Bund der Privatangestellten (ZK 64733). - French ed.: Bulletin d'informations de la Fédération internationale des employés et des techniciens (ZK 16029). - Engl. ed.: Newsletter of the International Federation of commercial clerical and technical employees (ZK 16028).